Role of the major histocompatibility complex class II protein presentation pathway in bone immunity imbalance in postmenopausal osteoporosis - Wang, Xiaoning; Zhang, Xin; Han, Yidan; Duan, Xinwei; Wang, Jianchang; Yan, Hui; Wang, Shanshan; Xu, Yunteng; Zhu, Zaishi; Wang, Lili; Huang, Yanfeng; Lin, Qing; et al. (Frontiers in Endocrinology, 2022)
Bone immunity regulates osteoclast differentiation and bone resorption, and is a potential target for the treatment of postmenopausal osteoporosis (PMOP). The molecular network between bone metabolism and the immune system is complex. However, the molecular mechanism underlying the involvement of the major histocompatibility complex class II (MHC-II) molecule protein presentation pathway in PMOP remains to be elucidated. The MHC-II molecule is a core molecule of the protein presentation pathway. It is combined with the processed short peptide and presented to T lymphocytes, thereby activating them to become effector T cells. T cell-derived inflammatory factors promote bone remodeling in PMOP. Moreover, the MHC-II molecule is highly expressed in osteoclast precursors. MHC-II transactivator (CIITA) is a main regulator of MHC-II gene expression and the switch for protein presentation. CIITA is also a major regulator of osteoclast differentiation and bone homeostasis. Therefore, we hypothesized that the MHC-II promotes osteoclast differentiation, providing a novel pathogenic mechanism and potential target for the treatment of PMOP.